Perbandingan Hasil Belajar Bahasa Arab Secara Online dan Offline pada Peserta Didik di Madrasah Tsnawiyah Dar Al-Dakwah Wa Al-Irsyad (DDI) Mattoanging Bantaeng - Fauziah, Sitti; Ilyas, Hamka; Aisyah Chalik, Sitti (Shaut al Arabiyyah, 2024)
This research is based on problems that occur in online learning that makes students and teachers experience obstacles and difficulties, until the madrasah makes a decision to apply offline learning (face to face) even though there is no government policy. This study aims to see the differences in the results of students' learning Arabic which is carried out online and offline. This research is a quantitative research in the form of expost facto research. The sample of this research is the students of Madrasah Tsanawiyah DDI Bantaeng, totaling 73 people. This study collects data using observation, interviews and documentation. The results of this study indicate that based on the results of calculations at the sig level, the results obtained are 0,09 ≥ 0,05. This result means that there is a comparison of online learning and offline learning on the learning outcomes of 8th grade students of Madrasah Tsanawiyah DDI Bantaeng with the average value of online learning. 83 and offline 84. Based on the above findings, it is hoped that educators will further broaden their horizons for the application of online learning.